Structural Characterization and Properties of Liquid Epoxidized Deproteinized Natural Rubber - Nguyen, Duc Manh; Nghiem, Thi Thuong (Old Journal, 2020)
The liquid epoxidized deproteinized natural rubber (LEDPNR) was prepared by epoxidation of deproteinized natural rubber with fresh peracetic acid 33 v/v% in latex stage followed by degradation with sodium nitrite (NaNO₂) kept hydrogen peroxide (H₂O₂) in acid medium. LEDPNR was characterized through FT-IR and 1D-NMR (¹H-NMR, ¹³C-NMR) spectroscopies. It was found that LEDPNR contains not only the typical structure of cis-1,4-isoprene but also epoxydized unit and trans-1,4-isoprene units derived from isomerization. Furthermore, hydroxyl groups are also detected and confirmed by NMR spectroscopy. DSC thermogram of samples shows that Tg of LEDPNR was higher than that of DPNR. This suggests that the interaction of polar groups in LEDPNR decreases the flexibility of natural rubber.